Research on terminal switch interval based on DTL - Yufei CUI; Jinwu WEI; Siyu PAN; Rongfang ZHANG; Xiao WANG; Zixiang JIA (Dianxin kexue)
With the rapid development of mobile internet, the population dividend of operators is gradually saturated, and the switch node of user mobile terminal has become the focus of operators’ attention. The switching frequency of users was predicted by decision tree algorithm based on the consumption information of user history and the replacement information of mobile terminals, which provided data support for the accurate marketing of mobile terminals and the stock management of users.